PENGEMBANGAN WEBSITE SIMEKAR MENGGUNAKAN METODE AGILE UNTUK PENINGKATAN EFISIENSI DAN EFEKTIVITAS KOLABORASI ORGANISASI - Rifki, Muhamad; Dwicahya Supriatman, Rian; Sidiq, Maulana (Fakultas Teknik Jurusan Sistem Informasi Universitas Galuh, 2024)
The development of the Simekar website (Cooperation Evaluation Monitoring System) aims to increase efficiency and effectiveness in collaboration between organizations. Agile methods are used in this development to allow for rapid adaptation to changing user and environmental needs. The study combines a flexible approach to software development with a focus on collaborative performance evaluation. Through the use of Agile, the iterative development process allows stakeholders to be actively involved in the entire development cycle, thus ensuring a solution that fits their needs. In the tests conducted, the Simekar website showed a significant improvement in the efficiency of tracking and evaluating organizational cooperation, as well as facilitating better communication between stakeholders. The results indicate that the use of Agile methods in Simekar website development can positively affect the efficiency and effectiveness of organizational collaboration, by providing a more responsive and adaptive platform to the dynamics of cross-organizational cooperation.